On naturalistic saltation genealogies of content: an exploration of continuity & discontinuity in nonreductive diachronic explanations of content by Adam H. Schroeder supervised by University of Cape Town - Schroeder, Adam (Department of Philosophy, 2025)
Explanations involving the relationship between naturalism, normativity and intentional content are often plagued with difficulty. Incorporating any two in an explanation usually leads to challenges with integrating the third. My thesis aims to explore this tension, by considering an ambitious version of naturalistic explanation for the emergence of normative intentional content. I wish to cast doubt on this explanation by showing how it fails to alleviate the aforementioned tension. In fact, I will argue that this explanation is inconsistent owing to the inimical relationship between naturalism, normativity and intentional content. The explanation I will be considering is one amongst a variety of naturalistic explanations for solving the placement problem, i.e., how to locate intentional content, or items involving intentional content, “in a world exhaustively characterized in terms of the … collective posits of the … sciences.” 1 Traditionally, the answer to this location problem has been pursued by trying to naturalise content. In general, this involves providing some reductive relation between content and accepted natural facts in the hope of demonstrating that content can be understood in completely naturalistic non-contentful terms. This strategy has faced several difficulties in relation to normativity such as the disjunction problem and gerrymandering objection inter alia. As a prophylactic measure to deal with these difficulties, a strategy has recently come into vogue which forgoes attempts to provide purely reductive explanations of content; rather, it aims to explain how it is possible for content to nonreductively emerge in the natural world. In other words, it aims to explain the natural origins of content, rather than naturalise content. I name accounts fitting this strategy Naturalistic Saltation Genealogies of Content. Despite the benefits this strategy affords in avoiding the perennial objections naturalisation projects face in relation to normativity, my aim is to show that it is susceptible to its own set of difficulties due to the tension between naturalism, normativity and intentional content. More specifically, my aim is to show that the central assumptions of this strategy are inconsistent, and as a result, entail that they are discontinuous explanations of content. Alternatively put, these genealogical explanations cannot succeed in answering the placement problem. A consequence of this aim will be that if one is committed to the continuity of a naturalistic saltation genealogy of content, then this can be shown to implicitly entail the reduction of the normative to the nonnormative or the use of some non-naturalistic resources in explanation. The aim and consequence of my argumentation can by captured by the following slogan: (S) Naturalistic saltation genealogies of content are either discontinuous explanations or implicitly entail the reduction of the normative to the nonnormative or the rejection of naturalism. This is the same as saying that: (S*) Naturalistic saltation genealogies of content are either discontinuous explanations or self-defeating. Whereby ‘self-defeating' I mean that proponents of these genealogies unwittingly revert to other strategies for solving the placement problem – strategies that naturalistic saltation genealogies of content were precisely aimed at avoiding. This slogan will be demonstrated to be a product of the structural objection named the Continuity-Discontinuity Regress Argument. I.e., for every continuous naturalistic saltation genealogy, there is a Discontinuity Argument against it; and for every Discontinuity Argument there must be a sub-continuous naturalistic saltation genealogy constructed in response. This sets off a regress which results in an infinite regress of location problems.